A diabetic woman with a swollen forearm - Alimohammad Fatemi; Golnaz Samadi; Ali Hekmatnia; Bijan Iraj; Mina Saber (Journal of Research in Medical Sciences, 2012)
Diabetic muscle infarction (DMI) is an unusual complication of diabetes mellitus. It is usually seen in long-standing diabetes mellitus. This article presents a case of DMI in the left forearm of a 58-year-old woman. She had a swollen forearm. The level of creatine kinase was 5930 U / L. Her condition was initially suspected for either cellulitis or venous thrombosis. A magnetic resonance imaging (MRI) study of the forearm showed diffuse edema and abnormal signals of the left forearm. The diagnosis of DMI was made. She was treated conservatively and her symptoms resolved within a short period of time. DMI should be considered as a differential diagnosis of any painful and swollen limb in diabetic patients.